Post-Pandemic Economic Recovery Through Cultural Diplomacy: The Case Of Indonesia’s Tourism Promotion In Russia - Wijaya, Bagaskara Sagita; Syuryansyah (JELAJAH: Journal of Tourism and Hospitality, 2025)
The COVID-19 pandemic caused a significant decline in international tourist arrivals to Indonesia, severelyimpacting the country’s tourism sector. In response, cultural promotion has emerged as a strategic tool in publicdiplomacy to aid economic recovery and attract foreign visitors, particularly from Russia. This study evaluates theeffectiveness of Indonesia’s cultural promotion efforts in Russia in revitalizing the tourism sector post-pandemic. Aqualitative case study approach was employed, utilizing document analysis and secondary sources from theMinistry of Tourism and the Ministry of Foreign Affairs. The findings reveal that Indonesia’s cultural promotioninitiatives—such as festivals, exhibitions, and digital media campaigns—have successfully generated interestamong Russian tourists. These programs have enhanced Indonesia’s visibility and cultural appeal, contributing to agradual increase in Russian tourist arrivals. However, challenges remain, including budget limitations, shiftinggeopolitical dynamics, and competition from other destinations. Despite these obstacles, public diplomacy plays avital role in shaping Indonesia’s international image, fostering bilateral relations, and supporting economic growththrough tourism. To further enhance the impact of cultural promotion, this study recommends strengtheninginstitutional collaboration between tourism and diplomatic agencies, optimizing digital-based promotionalstrategies, and diversifying cultural diplomacy initiatives to reach a broader audience. With the right policies andstrategic implementation, cultural promotion can serve as a key catalyst for the recovery of Indonesia’s tourismsector, ensuring long-term sustainability and economic resilience in the post-pandemic era.